PENGARUH PELAYANAN REFERENSI PERPUSTAKAAN PERGURUAN TINGGI BERBASIS DIGITAL TERHADAP MAHASISWA DAN FAKTOR-FAKTOR YANG MEMENGARUHI KEEFEKTIFAN PROSES PELAYANAN REFERENSI DI MASA PANDEMI COVID-19 (STUDI KASUS PERPUSTAKAAN INSTITUT PERTANIAN BOGOR) - Irzy Riandi Nugraha (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2021)
College libraries certainly have an important role in the course of the educational process in the tertiary institutions that oversee it. The services available in the library are used by students to fulfill their needs for information. These services are available directly so as to provide students who need library services as possible. However, during this pandemic, library services that are provided directly, of course, must comply in order to comply with the Covid-19 health protocol. Therefore, the library transfers all services that are directly related to library services, including digital, including reference services. This study uses a descriptive qualitative approach with the literature study method, the observation method to analyze and analyze how the influence of the digital-based Bogor Agricultural Institute library reference on students and to find and explain in detail what factors can influence the reference service process. so that it can form an effective reference. It was found that this digital-based reference service had an effect in particular on the effect of service and information control on student satisfaction if the results of the references received were in accordance with their needs and found that library material collections, library users, librarians and library staff, library facilities, library funds or budgets, management library as well as connection speed and stability of the internet network have a big influence on the realization of an effective digital-based reference service.